2022
DOI: 10.1186/s12889-022-13602-1
|View full text |Cite
|
Sign up to set email alerts
|

Financing COVID-19 vaccination in sub-Saharan Africa: lessons from a nation-wide willingness to pay (WTP) survey in Ghana

Abstract: Background Over 13 million doses of the corona virus disease, 2019 (COVID-19) vaccines have been administered in Ghana as at March, 2022; 28.5% of the population have received one dose while 16.3% have been fully vaccinated. Cost associated with COVID-19 vaccinations in low- and middle-income countries (LMICs) requires rethinking on sustainable funding arrangements to consolidate gains made towards containing the COVID-19 pandemic. Objective Ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…Here, it should be noted that resources for IEC activities could be diverted towards the relatively smaller proportion of people who need more awareness in understanding the importance of the COVID-19 vaccine. Most of the participants reported that the free vaccination provided by the government was a major reason to accept vaccines, which is in congruence with the findings of a web-based study which showed that only 55% of the study participants were willing to pay for the COVID-19 vaccine [24]. However, free vaccines hold importance in relation to global vaccine equity, as wealthier countries could quickly obtain vaccines.…”
Section: Discussionsupporting
confidence: 78%
“…Here, it should be noted that resources for IEC activities could be diverted towards the relatively smaller proportion of people who need more awareness in understanding the importance of the COVID-19 vaccine. Most of the participants reported that the free vaccination provided by the government was a major reason to accept vaccines, which is in congruence with the findings of a web-based study which showed that only 55% of the study participants were willing to pay for the COVID-19 vaccine [24]. However, free vaccines hold importance in relation to global vaccine equity, as wealthier countries could quickly obtain vaccines.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that hesitation about vaccines can strongly influence people’s WTP. 5 , 8 According to our findings, increasing parents’ WTP and reducing their hesitancy to vaccinate their children could help achieve full vaccination of children.…”
Section: Discussionmentioning
confidence: 70%
“… 4 Therefore, identifying the determinants associated with WTP is crucial for reducing the risk of recurrent widespread outbreaks. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, data collection for this study occurred outside the vaccine administration period. By the time mandatary face mask use requirements were lifted, 13.2 million vaccine doses were administered in Ghana (Alhassan et al ., 2022).…”
Section: Data and Contextmentioning
confidence: 99%